2010
DOI: 10.1016/j.ijdevneu.2010.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and the time window for the expression of the α8 nicotinic acetylcholine receptor in the membrane of chick retinal cells in culture

Abstract: We have previously shown that melatonin influences the development of alpha8 nicotinic acetylcholine receptor (nAChR) by measurement of the acetylcholine-induced increase in the extracellular acidification rate (ECAR) in chick retinal cell cultures. Cellular differentiation that takes place between DIV (days in vitro) 4 and DIV 5 yields cells expressing alpha8 nAChR and results in a significant increase in the ECAR acetylcholine-induced. Blocking melatonin receptors with luzindole for 48h suppresses the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Interestingly, luzindole blockage of the 5‐MCA‐NAT effects on cAMP (Sampaio, 2009) and on dopamine accumulation (present study) was observed in retinas at all developmental stages, while melatonin inhibitory effects on cAMP accumulation were not antagonized by luzindole in non‐differentiated retinas (Sampaio, 2008). This antagonist also hampers chick retinal cell differentiation (Sampaio et al, 2005; Sampaio and Markus, 2010); however, the mechanism by which melatonin triggers retinal differentiation remains unknown. Mel1a melatonin receptors are antagonized by luzindole, and thus, the participation of this type of melatonin receptor in 5‐MCA‐NAT effects is not probable because luzindole has no effect on Gi‐coupled melatonin membrane receptors in non‐differentiated retinas (Sampaio, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, luzindole blockage of the 5‐MCA‐NAT effects on cAMP (Sampaio, 2009) and on dopamine accumulation (present study) was observed in retinas at all developmental stages, while melatonin inhibitory effects on cAMP accumulation were not antagonized by luzindole in non‐differentiated retinas (Sampaio, 2008). This antagonist also hampers chick retinal cell differentiation (Sampaio et al, 2005; Sampaio and Markus, 2010); however, the mechanism by which melatonin triggers retinal differentiation remains unknown. Mel1a melatonin receptors are antagonized by luzindole, and thus, the participation of this type of melatonin receptor in 5‐MCA‐NAT effects is not probable because luzindole has no effect on Gi‐coupled melatonin membrane receptors in non‐differentiated retinas (Sampaio, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It has paracrine functions on dark vision improvement (Wiechmann and Sherry, 2013) and in the protection of retinal cells (Tosini et al, 2012). Additionally, this neurohormone promotes retinal differentiation in avian species (Sampaio et al, 2005; Sampaio, 2008; Sampaio and Markus, 2010). Beyond its ancestral free radical scavenger activity (Suzen, 2013), melatonin functions mainly via membrane Gi‐coupled receptors (MT1 and MT2 for mammalian and Mel1a, Mel1b, and Mel1c for avian; Dubocovich et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The 4-P-PDOT antagonist effect was shown to occur only after early synaptogenesis (embryonic day 14), and the luzindole antagonist effect was shown to occur only after retinal differentiation (2-days post-hatching) (Sampaio, 2008). The same developmental profile for the luzindole antagonist effect was found in differentiating retinal cells in culture (Sampaio et al, 2005;Sampaio and Markus, 2010). Here, rudimentary heart morphogenesis was not hampered by luzindole but it was by 4-P-PDOT, which was not capable of impeding optic cup formation.…”
Section: Melatonin Receptor Pharmacology In Developing Chick Embryosmentioning
confidence: 72%
“…In animal models, the Mel1c melatonin receptor has not been investigated in the developing chick retina, but the Mel1a and Mel1b melatonin membrane receptors were observed by immunofluorescence in differentiating chick whole retinas (Sampaio, 2013). A study using chick retinal cells in culture showed that the absence of melatonin or blockage of the melatonin receptors with luzindole, in a straight developmental time window that corresponded to the final part of retinal cell differentiation, hampered the appearance of functional homomeric nicotinic receptors (Sampaio et al, 2005;Sampaio and Markus, 2010). However, in developing chick retinas, the potency of the melatonin receptor antagonists luzindole and 4-P-PDOT was dependent on developmental stage in experiments where they were tested against melatonin inhibitory effects on both cyclic adenosine 3′,5′-monophosphate (cAMP) levels (Sampaio, 2008;Sampaio, 2009) and endogenous dopamine accumulation (Sampaio et al, 2014).…”
Section: Introductionmentioning
confidence: 99%